En torno a la filiación del texto del Bellum Gallicum de César en el manuscrito Escurialensis M.III.101 - Moreno Hernández, Antonio (Cuadernos de Filología Clásica. Estudios Latinos, 2005)
This article shows the critical analysis of Caesar’s Bellum Gallicum in the fourteenth-century manuscript Escurialensis M.III.10 (Z), in order to clarify its relationship with the textual tradition and establish its critical value. The examination of paratextual elements (tituli and colophons) and the collation of the variants leads to the conclusion that this manuscript belongs to the c family of a-class, and in particular to the same tradition of Parisinus Lat. 5056 (Q). It is proved that Z is related to other ms. of this family, the Parisinus Lat. 5767 (P), because Z and P come directly and independently from a common hyparchetype, closed to Q. It allows to reconstruct the history of this branch of the textual tradidion of B.G.